STN EN 736-1: 1999 (13 3001), Armatúry. Názvoslovie Časť 1 Definície typov armatúr - Rypák, Rudolf; Madár, Ján (Úrad pre normalizáciu, metrológiu a skúšobníctvo SR, 1999)
Táto národná norma je identická s EN 736-1: 1995